The Correlation between Self – Esteem and Student’s Reading Comprehension - Elsa Rosalina; Nasrullah Nasrullah (English Language Teaching Educational Journal, 2019)
The aim of this study was to know the correlation between self-esteem to student’s reading comprehension. This study employed quantitative approach in the form of correlation design to identify the correlation between self-esteem and students reading comprehension. The population of the present study was English department students of ULM academic year 2018/2019. Data collection involved 35 students who took part in the reading course. There are two kinds of the instrument used: test and questionnaire. The data in this study were analyzed by using Pearson product-moment. The result of the study reveals that there is a correlation between self-esteem and student’s reading comprehension. The result showed that the r of the first calculation was .0457. It meant that H0 was rejected and self-esteem has a correlation to the reading comprehension with significance tailed 0.006< 0.05